Qualitativ empirische Methoden in den Berufsfeldern der Sozialen Arbeit: Am Beispiel der individuellen Hilfeplanung des Landschaftsverbands Rheinland - Bärbel Schomers (IUBH Internationale Hochschule, 2020)
– This study aims to examine the relationship between methods from qualitative empiric research and their practical relevance in certain fields of social work. Research object and example is the assistance planning for disabled people. This text will answer a number of questions: Why do we need qualitative empirical knowledge in the various fields of social work? Which qualitative empirical methods are relevant? What skill sets are necessary for the observer and interviewer? The example of the individual help planning (IHP) authorized and granted by the Landschaftsverband Rheinland (LVR) allows examination and discussion of two important methods: the interview and the participative observation. To write a professional individual help planning, which aims are operationalized, it is necessary to take three different steps: the first phase of exploring, the second phase of interviewing and the third phase of postprocessing or editing. Best practices for collecting robust empirical data under every day field conditions in social work are identified. One example is to define behavioral rules to mitigate negative effects of the behavior of the observer and interviewer on the results, or to codify positive effects.
Keywords: 300; Soziale Arbeit; qualitative Empirie; Experteninterview; teilnehmende Beobachtung; Hilfeplanung